2000
DOI: 10.1590/s0041-87812000000100004
|View full text |Cite
|
Sign up to set email alerts
|

Müllerian adenosarcoma of the uterus with sarcomatous overgrowth following tamoxifen treatment for breast cancer

Abstract: Müllerian adenosarcoma with sarcomatous overgrowth presented by a 52-year-old female patient after adjuvant tamoxifen treatment for breast carcinoma is described. The diagnosis was made on histological basis after curettage and complementary total hysterectomy with bilateral salpingo-oophorectomy. The immunohistochemical study showed high expression of estrogen receptors in the epithelial component of the lesion and irregularly positive findings in the stroma. The proliferative activity evaluated by Ki-67 immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…[10] we also think that hormone receptors might play role in prognosis and be of significant clinical importance. Furthermore, some researchers had taken notice of the MASO cases occurring after tamoxifen therapy, suggesting a hormonal relationship [11]. Interestingly, endometrial curettage material of our case disclosed endometrial polyp with a hypercellular stroma, supporting this statement.…”
Section: Discussionsupporting
confidence: 80%
“…[10] we also think that hormone receptors might play role in prognosis and be of significant clinical importance. Furthermore, some researchers had taken notice of the MASO cases occurring after tamoxifen therapy, suggesting a hormonal relationship [11]. Interestingly, endometrial curettage material of our case disclosed endometrial polyp with a hypercellular stroma, supporting this statement.…”
Section: Discussionsupporting
confidence: 80%
“…The molecular mechanisms behind the development of uterine neoplasm of different histologies under tamoxifen therapy remain unexplained and further studies are needed. The mechanism of this increased risk is thought to be the estrogen agonist activity of tamoxifen on the uterus, which is similar to the mechanism for increased incidence of uterine cancer in women who take unopposed estrogen as hormone replacement therapy (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…This rare tumor was first described in 1974 and accounts for only 8% of all uterine sarcomas [1]. It has been suggested that primary müllerian adenosarcoma of the uterus may be associated with tamoxifen therapy [2,3].…”
mentioning
confidence: 99%